A Study on Community Economic Resilience in Response to Earthquakes in Jailolo Sub-District, North Maluku - Febriyanti Febriyanti; Santi Martini; Atik Choirul Hidajah; Febi Dwirahmadi (Jurnal Berkala Epidemiologi, 2021)
Background: The earthquake that hit the Jailolo sub-district in 2015 caused massive damage and loss. This catastrophic event affected not only impacted the local government's economy but also affected many communities, households and individuals living in these communities. Purpose: Aim of this study is to assess the economic resilience of communities in the Jailolo sub-district in response to earthquakes. Methods: This research was based on a descriptive observational study and employed a survey method to assess the economic resilience of communities in the Jailolo sub-district. The study was conducted in five villages, namely Tedeng, Payo, Saria, Matui, and Buku Maadu. The cut-off point for each indicator was classified as very high criteria (>1.05), high (0.95–1.05), moderate (0.85–0.94), low (0.74–0.84), and very low (≤0.73). Results: The proportion of community home ownership was found to be 100% (Resilience Factor Index (RFI)=1.67). The proportion of community work was 33.75% (RFI=0.68). The proportion of dual-income sources of communities in the Jailolo sub-district was 50.89% (RFI=1.02). The proportion of community income that exceeded the provincial minimum wage (PMW) was 8.71% (RFI=0.10). Based on the results of these indicators, the economic resilience of people in the Jailolo sub-district, which was obtained by considering the average RFI of each indicator, was 0.86. Conclusion: Community economic resilience in the Jailolo sub-district was found to be in the medium category. The highest and lowest resilience factors resulted from home ownership and income, respectively.